C is correct

S=(a+b*)*=(a*(b*)*)*=(a*b*)*

T=(a+b)*=(a*b*)* so S=T

S=(a+b*)*=(a*(b*)*)*=(a*b*)*

T=(a+b)*=(a*b*)* so S=T

The Gateway to Computer Science Excellence

First time here? Checkout the FAQ!

x

+14 votes

Let $S$ and $T$ be languages over $\Sigma=\{a.b\}$ represented by the regular expressions $(a+b^*)^*$ and $(a+b)^*$, respectively. Which of the following is true?

- $S \subset T$
- $T \subset S$
- $S = T$
- $S \cap T = \phi$

+24 votes

0

Can anyone explain in more detail? I am confused that regular expression S will generate more number of b's as compared to expression T. If they need to be equal they both should always generate same set of symbol but number of b's generated by expression S can be more.

Is this solution is an identity of regular expression? or we need to evaluate set of string and make the comparison.

Is this solution is an identity of regular expression? or we need to evaluate set of string and make the comparison.

+4 votes

0

Bt string abbbabbb is not accepted by T which is accepted by S...then how S=T?Please correct me if I m wrong...

- All categories
- General Aptitude 1.2k
- Engineering Mathematics 5k
- Digital Logic 2k
- Programming & DS 3.6k
- Algorithms 3.1k
- Theory of Computation 3.9k
- Compiler Design 1.5k
- Databases 2.9k
- CO & Architecture 2.5k
- Computer Networks 2.9k
- Non GATE 1k
- Others 1.4k
- Admissions 412
- Exam Queries 419
- Tier 1 Placement Questions 17
- Job Queries 55
- Projects 9

34,943 questions

41,958 answers

119,194 comments

41,472 users